Environmental impact of invertebrates for biological control of arthropods: methods and risk assessment - Bigler, F.; Babendreier, D.; Babendreier, D.; Bigler, F.; Kuhlmann, U.; Kuhlmann, U. (Wallingford :CABI Publishing, 2006)
This book, intended for the scientific community involved in biological control and integrated pest management, commercial companies producing biological control agents, risk assessors and regulatory authorities, compiles the current methodologies used for assessing the environmental impacts of invertebrate biological control agents and guidelines in performing science-based risk assessments required for the future regulation of such organisms.
Keywords: HH100 - Biological Control; ZZ900 - Techniques and Methodology